1970
DOI: 10.1149/1.2407684
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Impurities in Zn,O-Doped GaP Liquid Phase Epitaxy Layers

Abstract: A series of variously doped normalGaP liquid phase epitaxy (LPE) layers were analyzed to establish the distribution of Zn,O and residual impurities contributing to the net impurity gradient previously observed in the p‐layer of high efficiency normalGaP LPE diodes. From these experiments we conclude that the net impurity gradient is primarily a consequence of a decreasing Zn concentration along the growth direction, and, to a lesser degree, an increasing residual donor concentration. The distribution of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Values of xlzn for each melt were calculated by assuming the incorporation without loss of the total amount of Zn present in the Zn(POz)2. Figure 7 also illustrates the theoretical solubility isotherm for GaP at 1465~ in the immediate vicinity of Additional evidence to confirm the essential correctness of the low temperature isotherms is provided by the recent data of Saul and Hackett (29) on Zn incorporation in GaP, grown by liquid-phase epitaxy from an initial growth temperature of 1025~ and from a solution containing Xlzn = 3 x 10 -4. It has been shown by these authors that the Zn solubility in GaP, obtained by surface capacitance measurements and Zn ~5 tracer analysis, decreases from the growth interface (1025~ to the surface (~--770~ Furthermore, Saul and Hackett (29) have demonstrated by means of a detailed analysis that their experimental Zn distribution data (CSzn vs. distance from interface) compare favorably with the theoretical Zn profile calculated on the basis of the isotherms in Fig.…”
Section: Discussion Of Resultssupporting
confidence: 59%
“…Values of xlzn for each melt were calculated by assuming the incorporation without loss of the total amount of Zn present in the Zn(POz)2. Figure 7 also illustrates the theoretical solubility isotherm for GaP at 1465~ in the immediate vicinity of Additional evidence to confirm the essential correctness of the low temperature isotherms is provided by the recent data of Saul and Hackett (29) on Zn incorporation in GaP, grown by liquid-phase epitaxy from an initial growth temperature of 1025~ and from a solution containing Xlzn = 3 x 10 -4. It has been shown by these authors that the Zn solubility in GaP, obtained by surface capacitance measurements and Zn ~5 tracer analysis, decreases from the growth interface (1025~ to the surface (~--770~ Furthermore, Saul and Hackett (29) have demonstrated by means of a detailed analysis that their experimental Zn distribution data (CSzn vs. distance from interface) compare favorably with the theoretical Zn profile calculated on the basis of the isotherms in Fig.…”
Section: Discussion Of Resultssupporting
confidence: 59%
“…As the doping precursor is switched off, the finite doping concentration in the droplet will gradually reduce to negligible values, which can only be accomplished through the gradual deposition of the 'stored' dopants in NW segments that are not intended to be doped. This effect is present in systems that crystalize from liquids, has been known for decades in liquid phase epitaxy, 60 and was recently discussed in the context of axial heterostructure NW growth. 61,62,63 In their LEAP studies, Connell et al also identified such doping gradients in a Ge NW as shown in Figure 7.…”
Section: Dopant Incorporation and Gradients During Nanowire Growthmentioning
confidence: 92%
“…The addition of Ga203 results in compensation of Zn acceptors equivalent to an increase in donor concentration of 2.7 • 1017 atoms/cm 3, which has been interpreted to be entirely due to the deep O donor (9). To substantiate this interpretation, an O-doped LPE layer was grown using the same Ga~O3 addition.…”
Section: Residual Oxygenmentioning
confidence: 99%
“…Both Zn-and Zn,O-doped layers were grown on Tedoped (ND--NA~8 • 1017 ) SG or LEC (liquid encapsulation Czochralski) substrates using a fused quartz sealed-tube LPE system which has been described elsewhere (9). Except where indicated, layers were grown in evacuated ampoules which were cooled from 1025 ~ to 600~ at a rate of 10~…”
mentioning
confidence: 99%